A Tautomeric [lamda]3/[lambda]5-phosphane pair and its ambiphilic reactivity - Mörsdorf, Jean-Marc; Wadepohl, Hubert; Ballmann, Joachim (Inorganic chemistry, 2019)
The central phosphorus atom of a novel hydroxyl-functionalized triarylphosphane was shown to reversibly insert into one of the molecule’s O-H bonds, which forms the basis for a tautomeric λ3/λ5-phosphane equilibrium. For the first time, this equilibrium was detected for a λ3-triarylphosphane and the underlying dynamic process was elucidated by NMR spectroscopy. On the basis of reactivity studies, a nucleophilic character was assigned to the minor species present in solution, the λ3-phosphane. Upon methylation, for example, the λ3-form was selectively removed from the equilibrium and converted to the corresponding phosphonium salt. However, upon generation of an alkoxide via proton abstraction, the electrophilic character of the λ5-phosphane in the equilibrium became evident since the alkoxide was found to attack the molecule’s phosphorus atom. This intramolecular reaction led to the selective formation of a new anionic λ6-hydridospirophosphane.